Asthma and exercise-induced bronchoconstriction in amateur endurance-trained athletes - Kippelen, P.; Caillaud, C.; Coste, O.; Godard, P. (International Journal of Sports Medicine, 2004)
High-level endurance training contributes to the development of asthma and exercise-induced bronchoconstriction but the effect of moderate endurance training on airway function remains to be determined. The aim of this study was to evaluate the prevalence of physician-diagnosed asthma and/or exercise-induced bronchoconstriction in moderately endurance-trained athletes. Ninety-five Mediterranean amateur endurance-trained athletes filled out a questionnaire about respiratory disorders and underwent a resting spirometry. Mean training volume was 10 h per week. The prevalence of asthma was found to be 4.2 %. All the athletes with asthma plus another one (5.3 %) reported having exercise-induced bronchoconstriction. These percentages are in the same range as those from the general population and much lower than those observed in elite endurance athletes. In contrast to elite athletes, our amateur endurance-trained athletes seem not exposed to a higher risk of asthma or exercise-induced bronchoconstriction than the general population. We suggest that 10 h per week of moderate endurance training in a temperate climate area does not lead to respiratory disease.